Fish and fishing gears of the Bangkau Swamp, Indonesia - . Irhamsyah; . Ahmadi; . Rusmilyansari (Journal of Fisheries, 2017)
This study contributes to the knowledge of traditional fishing gears and the weight-length relationship of fish species from the Bangkau Swamp, Indonesia. Although the use of fishing gears in Bangkau swamp complies with the local regulation but still, some weaknesses have been identified and the options for improvements are being proposed. The length-weight relationship of three dominant fish species, Channa striata, Trichogaster trichopterus, and T. pectoralis were analyzed. The b values ranged from 1.531 to 2.646, with R2 values ranged from 0.814 to 0.917 indicating negative allometric growth pattern; the species becomes leaner as the length increases. The food availability and temperature may have an effect on the growth pattern since the fishes were sampled in dry season. To the best our knowledge, this study is the first reference on WLR for swamp fish in the Bangkau village.